Ultrafiltration Membranes Functionalized with Polydopamine with Enhanced Contaminant Removal by Adsorption. Issue 5 (3rd February 2017) - Capozzi, Luigi C.; Mehmood, Farrukh M.; Giagnorio, Mattia; Tiraferri, Alberto; Cerruti, Marta; Sangermano, Marco
Abstract : The performance of polymeric ultrafiltration membranes functionalized with polydopamine to couple depth adsorption of contaminants with the typical surface rejection characteristics of the membrane is investigated. Methylene blue is used as the representative target contaminant to study the enhancement of membrane adsorption behavior, and its removal is investigated both in batch and under filtration conditions. The saturated membranes are completely regenerated and reused without loss of performance by cycling in acidic and alkaline solutions. Abstract : The performance of polymeric ultrafiltration membranes functionalized with polydopamine to couple depth adsorption of contaminants with the typical surface rejection characteristics of the membrane is investigated. Two approaches are deployed to achieve this functionalization: in a two‐step method, the ultrafiltration membranes are initially fabricated by phase inversion, then followed by coating with polydopamine; in a more facile and advantageous one‐step method, the membranes are subjected to phase inversion in a water solution containing dopamine, so that polymer precipitation and polydopamine functionalization occur at the same time. Methylene blue is used as the representative target contaminant to study the enhancement of membrane adsorption behavior, and its removal is investigated both in batch and under filtration conditions. The sorption capacity increases with increasing polydopamine coating time and is higher for the membranes fabricated via the one‐step protocol. The amount of methylene blue adsorbed per unit of membrane mass is large (roughly 5–10 mg g −1 ) and the kinetics of adsorption is fast. These characteristics allow these materials to get operated effectively and for long times in membrane filtration processes before stopping the system for regeneration. The saturated membranes are completely regenerated and reused without loss of performance by cycling in acidic and alkaline solutions.